Working theory : an analysis of the use and misuse performance tools - Kawitzky, Roxy (Department of Drama, 2016)
In this paper, I work through some of the theoretical and practical research concerns which have emerged during my MA in Theatre Making, including the Minor, Medium and Major projects developed as part of its coursework component. I begin with an outline of my core hermeneutic lenses, describing the relationship between the expressive faculties of the brain, voice and body in performance articulation, advocating for their de-conventionalisation within theatrical modes, and indicating a more diverse range of possibilities for these performance tools. I then describe the three primary examples I will be using in my explication, and relate each to a specific chapter; Siri Hustvedt's novel The Blazing World is discussed in the chapter of the Brain, and used to speak about the relationship between an expressed, materialised art object, and its invisible progenitor or counterpart which exists privately in the mind of the artist. Boris Nikitin's Woyzeck is discussed in terms of its approach to representation and communication, and the peculiar relationship it establishes between audience and performer. Finally, I talk about my Medium Project Journey from the Centre of the Earth in a consideration of the bodily and ethical implications of participatory performance practice, before beginning to describe my final production, CLOAKS, and concluding.